Deficiencies of macronutrients on nutritional status of castor bean cultivar Iris - Junior, José Lavres; Boaretto, Rodrigo Marcelli; Silva, Maria Lígia de Souza; Correia, Diva; Cabral, Cleusa Pereira; Malavolta, Eurípedes (Pesquisa Agropecuaria Brasileira, 2005)
The objectives of this work were to evaluate the effect of macronutrient deficiencies on growth and on nutritional status of castor beans (Ricinus communis L.), and to obtain the symptoms of the lack of N, P, K, Ca, Mg and S. Nutrient solutions containing all macronutrients and those from which one of these elements was omitted were the treatments used. The following determinations were made: chlorophyll (indirectly), nitrate reductase activity, NO3--N, H2PO4--P and K+, both on soluble fractions, and by spot tests. Deficiencies of N, Ca, S and Mg were the most limiting for dry matter production, followed in decreasing order by those of K and P. The highest concentrations of macronutrients were measured in roots and lower leaf blades. Critical levels of N and Ca in the upper leaf blades and of Mg in lower petioles were respectively, 46.7, 13.8, 6.5 g kg-1. Deficiencies affected chlorophyll meter readings. Nitrate reductase activity was correlated with chlorophyll readings. Soluble contents of N, P and K in the leaves were lower in plants deficient in the respective element. The same was found when spot tests were applied on the leaf sap.